A new class of draw solutions for minimizing reverse salt flux to improve forward osmosis desalination - Nguyen Thi Hau (2023)
The applications of forward osmosis (FO) have been hindered because of the lack of an optimal draw solution. The reverse salt flux from the draw solution not only reduces the water flux but also increases the cost of draw solute replenishment. Therefore, in this study, Tergitol NP7 and NP9 with a long straight carbon chain and low critical micelle concentration (CMC) were coupled with highly charged ethylenediaminetetraacetic acid (EDTA) as an innovative draw solution to minimize reverse salt diffusion in FO for the first time. The results showed that the lowest reverse salt flux of 0.067 GMH was observed when 0.1M EDTA-2Na coupled with 15mM NP7 was used as a draw solution and deionized water was used as a feed solution in FO mode (active layer facing with the feed solution). This is due to the hydrophobic interaction between the tails of NP7 and the FO membrane, thus creating layers on the membrane surface and constricting the FO membrane pores. Moreover, 1M EDTA-2Na coupled with 15mM NP7 is promising as an optimal draw solution for brackish water and sea water desalination. Average water fluxes of 7.68, 6.78, and 5.95 LMH were achieved when brackish water was used as a feed solution (5, 10, and 20g/L NaCl), and an average water flux of 3.81 LMH was achieved when sea water was used as a feed solution (35g/L NaCl). The diluted draw solution was recovered using a nanofiltration (NF-TS80) membrane with a high efficiency of 95% because of the high charge and large size of the draw solution.